The two-minute walk test in persons with multiple sclerosis: Correlations of cadence with free-living walking do not support ecological validity - Karle, Viktoria; Hartung, Verena; Ivanovska, Keti; Mäurer, Mathias; Flachenecker, Peter; Pfeifer, Klaus; Tallner, Alexander (International Journal of Environmental Research and Public Health, 2020)
The two-minute walk test (2MWT) is a frequently used walking capacity test in persons with multiple sclerosis (pwMS). However, less is known about its relevance with regards to walking capacity during free-living walking performance. Therefore, the ecological validity of the 2MWT was tested by 1. computing free-living minutes with the same intensity (cadence) as during the 2MWT and 2. investigating the relationship between 2MWT cadence and minutes with the same cadence during free-living walking. 20 pwMS aged 44.2 ± 12.2 (Expanded Disability Status Scale (EDSS) score of 3.1 ± 1.4) performed a 2MWT and wore an accelerometer for seven days. The number of pwMS reaching 100%, 90%, 80% or 70% of 2MWT cadence for at least one minute a day and minutes/day with at least 100%, 90%, 80% and 70% of 2MWT cadence during free-living walking was calculated. Six participants reached 100% of the 2MWT cadence for at least one minute/day during free-living walking. A total of 80% 2MWT cadence was the first intensity category that was reached by all participants during free-living walking. No significant correlation was found between cadence in the 2MWT and minutes in which this cadence was reached during free-living walking. Ecological validity with regard to walking intensity could not be confirmed in our study sample.
CRIS-Team Scopus Importer:2020-12-18
Keywords: Accelerometry; Ecological validity; Free-living walking; Habitual walking; Multiple sclerosis; Two-minute walk test; Walking performance